2016
DOI: 10.1016/j.nedt.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of education in the recognition and management of deteriorating patients: A systematic review

Abstract: Educational interventions designed to improve the recognition and management of patient deterioration can improve learner outcomes when they incorporate medium to high-fidelity simulation. High-fidelity simulation has demonstrated effectiveness when delivered in brief sessions lasting only forty minutes. In situ simulation has demonstrated sustained positive impact upon the real world implementation of rapid response systems. Outcome measures should include knowledge and skill developments but there are import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…However, the review also concludes that EWS updates require educational approaches that go beyond merely improving knowledge levels and should focus on outcome‐based training (Saab et al, ). The emphasis therefore of any update should be on developing experience and expertise rather than knowledge (Rattray, Crocker, Jones, & Connaghan, ) and simulation training should be used (Connell et al, ) as part of a team collaboration. Multidisciplinary‐focused education programmes have proven effective (Merriel et al, ), and nurses welcome education in collaboration with doctors to develop teamwork and communication relationship (Petersen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the review also concludes that EWS updates require educational approaches that go beyond merely improving knowledge levels and should focus on outcome‐based training (Saab et al, ). The emphasis therefore of any update should be on developing experience and expertise rather than knowledge (Rattray, Crocker, Jones, & Connaghan, ) and simulation training should be used (Connell et al, ) as part of a team collaboration. Multidisciplinary‐focused education programmes have proven effective (Merriel et al, ), and nurses welcome education in collaboration with doctors to develop teamwork and communication relationship (Petersen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Developments in education and training using both simulation training, teamwork and communication methods have been found to be beneficial for nurses and have a positive impact on EWS practice (Connell et al, ; Liaw et al, ; Ludikhuize, Jonge, & Goossens, ). In addition, the introduction of electronic systems that alert the critical care team from the patient's score has been shown to assist in improving response times and early patient management (Bellomo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…115 However, in the latter, the educational intervention was accompanied by greater use of a MET review, more vital signs documentation and a new TTS. Connell et al 116 included 13 studies evaluating the impact of educational programmes on doctors and nurses and all except one study showed either a change in behaviour or increased knowledge and confidence post training. This review also included the before-and-after study by Fuhrmann et al 114 showing no change in hospital mortality.…”
Section: Continuing Educationmentioning
confidence: 99%
“…Over the past decade, several published studies have examined the effectiveness of educational interventions on early recognition and management of clinical deterioration among nurses (Connell et al, ). Simulation was reported in more than half of these educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In crew resource management training, exercises and simulation are employed as approaches to emphasize the importance of human behaviours on safety and error reduction (Flin & Maran, 2015). (Connell et al, 2016). Simulation was reported in more than half of these educational interventions.…”
Section: Ta B L E 6 Multiple Linear Regression Coefficients For Modelmentioning
confidence: 99%